2019
DOI: 10.1038/s41467-019-09034-y
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered bacterial vesicles as biological nano-heaters for optoacoustic imaging

Abstract: Advances in genetic engineering have enabled the use of bacterial outer membrane vesicles (OMVs) to deliver vaccines, drugs and immunotherapy agents, as a strategy to circumvent biocompatibility and large-scale production issues associated with synthetic nanomaterials. We investigate bioengineered OMVs for contrast enhancement in optoacoustic (photoacoustic) imaging. We produce OMVs encapsulating biopolymer-melanin (OMV Mel ) using a bacterial strain expressing a tyrosinase transgene. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(147 citation statements)
references
References 69 publications
4
143
0
Order By: Relevance
“…The obtained results indicated that upon NIR light irradiation bacteria vesicles with melanin generated strong optoacoustic signals appropriate for bioimaging applications. In addition, the developed bacteria vesicles released heat upon NIR-laser irradiation, which resulted in photothermal effects both in vitro and in vivo [252].…”
Section: Bacteria-based Drug Carriersmentioning
confidence: 99%
“…The obtained results indicated that upon NIR light irradiation bacteria vesicles with melanin generated strong optoacoustic signals appropriate for bioimaging applications. In addition, the developed bacteria vesicles released heat upon NIR-laser irradiation, which resulted in photothermal effects both in vitro and in vivo [252].…”
Section: Bacteria-based Drug Carriersmentioning
confidence: 99%
“…Photothermal conversion is one of the main commercialized applications for solar energy harvesting . Photothermal materials directly convert solar light into heat immediately, which have been widely used in water evaporation and cancer therapy . There are two definitive advantages related to the introduction of photothermal effect (PE) into catalytic processes.…”
Section: Introductionmentioning
confidence: 99%
“…We have also validated how 64 Cu-YbT can potentially be used to advance bacterial therapies using engineered bacteria. Advances in genetic engineering have enabled us to explore the potential of using bacteria, particularly for cancer therapy in the last two decades 31,[48][49][50][51] . One of the most notable initial studies tested genetically engineered Salmonella for its anticancer activity in mouse models of subcutaneously implanted B16F10 melanoma tumors 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Optical imaging techniques based on bioluminescence and fluorescence have the inherent drawback of limited light penetration, unlike PET imaging which is depth independent. Recently, tumour localization of OMVs from E. coli was confirmed via photoacoustic imaging 48 . While the study described a novel strategy to specifically image the presence of OMVs in the body, it involved an additional step of vesicle design to make it amenable for optoacoustic imaging.…”
Section: Discussionmentioning
confidence: 99%